Anachronistic America: Nostalgia and Modernism, 1920-1950 - Semkiu, Joseph. (2018)
Abstract: American artists during the interwar period grappled with the radical technological, social, and economic changes of the second quarter of the twentieth century by turning to the past and allowing the anachronistic to seep into their art, by employing past visual tropes, antiquated subjects, and outmoded painting techniques. Edward Hopper, Grant Wood, and John Atherton all echoed different moments of the American past to inform their modern paintings with a sense of the uncanny and the nostalgic. Hopper looked at the Victorian Era for his 1925 canvas, The Bootleggers, Wood turned to the Hudson River School for his 1935 painting, Death on Ridge Road, and Atherton was inspired by the armor collection at the Metropolitan Museum of Art, as well as the American Surrealist movement in the 1930s, for his wartime, Invasion paintings. The anachronistic, time that is out of joint, highlights the nostalgic tone of these three artists' work, in which the artists yearn for a pre-Depression and pre-Second World War era. The three case studies provide further understanding to the sense of the outdated found within the American figurative tradition in the early twentieth century, as these artists attempted to create art that was rooted in the America past but was, ultimately, wholly modern.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Art and Art History.; Advisor: Eric Rosenberg.; Keyword: Art history.